Schlieren visualization of flow-field modification over an airfoil by near-surface gas-density perturbations generated by a nanosecond-pulse-driven plasma actuator. (9th May 2017) - Komuro, Atsushi; Takashima, Keisuke; Konno, Kaiki; Tanaka, Naoki; Nonomura, Taku; Kaneko, Toshiro; Ando, Akira; Asai, Keisuke
Abstract: Gas-density perturbations near an airfoil surface generated by a nanosecond dielectric-barrier-discharge plasma actuator (ns-DBDPA) are visualized using a high-speed Schlieren imaging method. Wind-tunnel experiments are conducted for a wind speed of 20 m s −1 with an NACA0015 airfoil whose chord length is 100 mm. The results show that the ns-DBDPA first generates a pressure wave and then stochastic perturbations of the gas density near the leading edge of the airfoil. Two structures with different characteristics are observed in the stochastic perturbations. One structure propagates along the boundary between the shear layer and the main flow at a speed close to that of the main flow. The other propagates more slowly on the surface of the airfoil and causes mixing between the main and shear flows. It is observed that these two heated structures interact with each other, resulting in a recovery in the negative pressure coefficient at the leading edge of the airfoil.